Cognitive Behavior Therapy Intervention for Parents of Autistic Children: Building Trust & Openness to the Environment - Bandoro, Galang Herlambang; Aprilia , Imas Diana (Angstrom Centre of Education, 2024)
This research aims to provide a comprehensive overview of the implementation of Cognitive Behavior Therapy (CBT) intervention in assisting parents in enhancing their trust and openness attitudes. The research methodology employed a qualitative approach with a case study method. The study focused on a single-family subject with a child on the autism spectrum. The CBT technique utilized was cognitive restructuring, comprising four steps: identifying the root problem, recognizing emerging feelings, managing erroneous or negative thought patterns, and forming new thought patterns. The treatment spanned four days, consisting of four sessions. The research findings indicate that through the application of CBT, parents experienced a shift in their attitudes towards understanding, awareness, and initiating interaction with their autistic child within the home environment in line with trust and openness towards their surroundings. However, parents have yet to consistently exhibit the trust they possess and still attempt interactions in environments of limited scope or low traffic, thus necessitating the need for parental trust management and consistency.